Analisis Perkembangan BUMDes se Kabupaten Tolitoli - Fitriyah Astri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
BUMDes are the economic drivers of rural communities that are managed by communities appointed through village meetings in an effort to strengthen the village economy and are formed based on the needs and potential of the village. This study aims to determine the development of BUMDes in Tolitoli Regency. The research approach used is descriptive quantitative. By using data collection techniques through interviews with informants who are considered to have the potential to provide information about BUMDes development from various aspects of institutions, regulations, BUMDes businesses, reporting administration and accountability, capital and assets. also through interviews and office administration documentation and accountability. The results show that in the classification most of them are at the growth classification level and some are in the basic classification. Factors that should be improved and receive attention for the development of BUMDes are to immediately improve the system starting from institutions, utilization of capital and assets, administration, and BUMDes regulations. Keywords: Village Business Institutions, Development